Isolation and Identification Candida spp from Urine and Antifungal Susceptibility Test - Othman, Karwan Ismael; Abdullah, Shorsh Mustafa; Ali, Belan; Majid, Mjda (Iraqi Journal of Science, 2018)
Candida ssp are of medical importance because they are the most common opportunistic mycosis worldwide, a common cause of nosocomial urinary tract infections (UTIs), oral candidiasis and genitourinary candidiasis. The development of Candida spp infection depends on several factors such as age, sex, and immunity of the host-pathogen relationship. They are resistance to one or more antifungal. The purpose of these studies to isolation and identification of Candida spp from urine sample and investigation of susceptibility of these strains to Amphotericin B andFluconazole. There are 105 Urine sample of the renal failure were collected using a sterile urinary cap, different diagnostic techniques were used for characterization of Candida spp. Culture characteristic, gram stain, Germ tube, CHROM agar candida and scanning electronic microscopic. Results showed 40% urine sample positive also Different Candida spp isolated, C. albicans (20%), C. parapsilisos (20%), C. glabrata (32.72%), and C. krusei (27.27%). The antibiotic susceptibility test of the isolates was determined by the Kirby-Bauer disk diffusion method. Candida spp sensitivity to 6µg/ml Amphotericin B but Fluconazole was ineffective against Candida spp. The most common pathogen in Urinary tract system is Candida spp both Albicans and non-Albicans are unusual causes of urinary tract infections in healthy individuals also Candida spp resistance to Fluconazole but sensitivity to low concentration Amphitericin B.